Dietary fat and calcium level effect on feedlot performance and carcass merit in steers - B. Bock; Robert T. Brandt Jr.; D.L. Harmon (Kansas Agricultural Experiment Station Research Reports, 1989)
Feeding fat increased feed intake and average daily gain, but feed efficiency was not affected. Feeding high levels of calcium (.9%) had no overall effect, but may tend to increase intake when fed with diets that contain primarily vegetable fat or highly unsaturated fat products.
Keywords: Cattlemen& #x27; s Day; 1989; Kansas Agricultural Experiment Station contribution; no. 89-567-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 567; Beef; Fat; Performance; Carcass Merit; Steers; Calcium